2016
DOI: 10.1097/j.pain.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain in adolescence and internalizing mental health disorders

Abstract: Chronic pain in childhood and adolescence has been shown to heighten risk for depressive and anxiety disorders in specific samples in adulthood; however, less is known about the association between a wider variety of chronic pains and internalizing mental health disorders. Using nationally representative data, the objectives of this study were to establish prevalence rates of internalizing mental health disorders (anxiety and depressive disorders) among cohorts with or without adolescent chronic pain, and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
138
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(151 citation statements)
references
References 34 publications
11
138
1
1
Order By: Relevance
“…Findings of the most recent epidemiological study by Noel et al [18] revealed a consistent pattern. The study conducted a secondary data analysis of a sample of 14,790 individuals from the National Longitudinal Study of Adolescent to Adult Health to examine the co-occurrence of adolescent chronic pain and lifetime rates of mental health disorders [18].…”
Section: Epidemiology Of Internalizing Mental Health Disorders In supporting
confidence: 54%
See 3 more Smart Citations
“…Findings of the most recent epidemiological study by Noel et al [18] revealed a consistent pattern. The study conducted a secondary data analysis of a sample of 14,790 individuals from the National Longitudinal Study of Adolescent to Adult Health to examine the co-occurrence of adolescent chronic pain and lifetime rates of mental health disorders [18].…”
Section: Epidemiology Of Internalizing Mental Health Disorders In supporting
confidence: 54%
“…Findings of the most recent epidemiological study by Noel et al [18] revealed a consistent pattern. The study conducted a secondary data analysis of a sample of 14,790 individuals from the National Longitudinal Study of Adolescent to Adult Health to examine the co-occurrence of adolescent chronic pain and lifetime rates of mental health disorders [18]. In contrast to previous research, a broader range of chronic pain conditions (i.e., headache, abdominal and musculoskeletal pain) were assessed in adolescence, and lifetime history of mental health disorders (i.e., depressive and anxiety disorders) were subsequently assessed in adulthood.…”
Section: Epidemiology Of Internalizing Mental Health Disorders In supporting
confidence: 54%
See 2 more Smart Citations
“…The current findings point to children’s pain memories as one potential mechanism that may underlie the persistence of pain; however, future longitudinal research is needed to further disentangle this relationship. Given the increasing prevalence (King et al, 2011) and burden (Groenewald, Wright, & Palermo, 2015) of pediatric chronic pain and its adverse impact on mental and physical health into adulthood (Noel, Groenewald, Beals-Erickson, Gebert, & Palermo, 2016; Shelby et al, 2013), this research could inform the development of cognitive-behavioral interventions to alter this course.…”
Section: Discussionmentioning
confidence: 99%